Block Chain Technology (Trinity Journal of Management, IT & Media (TJMITM), 2022)
Blockchain technology is revolutionary.  Blockchain Technology will bring revolution within the areas of accounting, e-Government, Finance, BPM, insurance, amusement, trading platforms, healthcare, Internet-of-Things, further as law corporations. Blockchain Technology includes a vast potential in introducing innovative solutions, reckoning on the realm or the world of its implementation, since economic potency and social advantages may be achieved through technical innovation and applications.
Keywords: Blockchain Technology; Blockchain; bitcoin; crypto currency; Ethereum; bitcoin mining; Coinbase; bitcoin trading